Análisis e interpretación a los estados financieros de la cooperativa de transportes Zamora Chinchipe durante los periodos 2014- 2015. - Curipoma Cuenca, Majheny Beatriz (2018)
The present thesis work was carried out with the purpose of evaluating the financial performance of the Cooperativa de Transportes "Zamora Chinchipe" which will help the leaders to make the correct decisions; To self with the purpose of complying with one of the requirements established in the Regulations of Academic Regime, prior to choosing the degree of Accounting and Audit Engineer, Public Accountant Auditor. The stated objectives could be met; so it was started with an interview with the Manager and Accountant, to collect truthful and timely information on the Financial Statements and more supporting documents for the years 2014-2015; then the application of vertical analysis, horizontal analysis and the application of indexes or financial ratios according to the economic need of the Cooperative as the Liquidity, Activity, Leverage and Profitability; Also, the presentation of a financial analysis report that allows its owners to make the right decisions. Finally, it can be concluded that through the application of the Financial Analysis Tools, it was established that the "Zamora Chinchipe" Transport Cooperative has a high capital of its own and that the Earned Income is not generating a good Financial Return. The report presented will serve its Administrators as help for the development of it.